SOCIAL ISOLATION AND ACCEPTANCE OF E-LEARNING IN THE TIME OF COVID-19 PANDEMIC - Weri Aprilia; Wing Wahyu Winarno (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2022)
The COVID-19 pandemic has led to social distancing. However, with the help of technology, the education world can get through this difficult time through virtual learning methods (e-learning). The aim of this study was to show how well the UTAU framework explains the behavioral drivers of e-learning system use by adding relevant variables, namely the moderating effects of social isolation and corona fear. This study takes accounting students as a sample and adopts a targeted sampling method. The sample size is 203 respondents, but eligible individuals can only process 195 samples. This study uses a quantitative method using the data analysis technique of SEM-PLS by WarpPLS 7.0 software. The results of the study showed that the variables of PE, SI, FC and Social Isolation are proven to have an effect on the intention to use e-learning among accounting students. Meanwhile, the EE variable was not proven to be supported as the effect on the intention to use e-learning. The results of the Corona Fear modification as a moderating variable has been shown to strengthen the relationship between PE, EE, and FC variables on intention to use e-learning.